Determinants of Hospitalization Costs among Moderate Cases of COVID-19 - BinBin Li MD; LaiTe Chen MD; Lu Shi PhD (SAGE Publishing, 2022)
Objective: To estimate demographic predictors of medical expense in hospitalization of moderate COVID-19. Methods: From January to March 2020, a total of 39 patients were treated and recovered from COVID-19 in a tertiary medical center in East China. Detailed cost data were collected and we estimated the demographic predictors of both total hospital expense and daily hospital expense. Results: The mean medical expense for treating hospitalized moderate COVID-19 cases was $1177.81. Every additional year in the patient's age corresponds to .9% more in total hospital expense (Coef. = 0.009, 95% CI 0.002-0.017, P < 0.01). The difference in daily medical expense between age groups was not statistically significant. Conclusions: Hospitalization cost was significantly elevated among the older patients, and the age effect in cost was mainly driven by the longer length of stay in the hospital. From a cost-saving perspective, the elderly population might deserve priority consideration when COVID-19 vaccination programs are implemented.